2017
DOI: 10.5539/jmsr.v6n3p20
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Strength of Pilot-Scale-Produced Water-Washed Cottonseed Meal in Comparison with a Synthetic Glue for Non-Structural Interior Application

Abstract: Water-washed cottonseed meal (WCSM) has been shown the potential to be used as renewable and environmentfriendly adhesives in wood products industry. Recently, WCSM was produced from defatted meal in a pilot scale. In this study, we initially compare the adhesive strength of the pilot-produced WCSM with that of a synthetic glue Vinavil 2259 L. WCSM may be used as the conventional D1 wood adhesives for nonstructural interior application per European standard EN204/205. Non-structural D3 type adhesives is more w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Indeed, the hot shear strength of the fir strips bonded by 0.5-mm cyclone was lower than the dry shear strength of the fir strips bonded by the same WCSM product. Little or negative impact of heat exposure on the adhesive strength of WCSM has also been observed previously with beech thin board [ 21 ].…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Indeed, the hot shear strength of the fir strips bonded by 0.5-mm cyclone was lower than the dry shear strength of the fir strips bonded by the same WCSM product. Little or negative impact of heat exposure on the adhesive strength of WCSM has also been observed previously with beech thin board [ 21 ].…”
Section: Resultssupporting
confidence: 63%
“…For general plywood and composite board bonding, a shorter fixed press time (3.6–6.0 min) has been used in the literature [ 16 , 42 , 44 ]. On the other hand, variable press times have also been used to evaluate the adhesives per European Union standards, such as 5, 15, 25 min in Nordqvist et al [ 45 ], and 30 min in He and Chiozza [ 21 ]. As a matter of fact, per our industrial partner’s input, 60-, 120- and 180-min press times have been applied in the evaluation of WCSM as a glue for bonding small wood items, such as the pencil sandwich slats in pencil making [ 19 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the utilization of defatted cottonseed meal as a valuable industrial stock feed and a fertilizer needs to be further exploited (Grevellec et al, 2001;Grewal and Khare, 2017;He and Cheng, 2017;Swiatkiewicz et al, 2016). Recent work (Cheng et al, 2013;He et al, 2014a;2014b;He and Chiozza, 2017) has shown that two cottonseed meal products, washed cottonseed meal (WCSM) and cottonseed protein isolate (CSPI), could be used as "green" wood adhesives. He et al (2016c) further scaled up the production of WCSM and co-products from laboratory 10-g levels to pilot production levels of 10-lb (4.54 kg) starting material.…”
Section: Introductionmentioning
confidence: 99%
“…Cottonseed meal was extracted with water or phosphate buffer [41,42], and the resulting cottonseed meal was found to be a lower cost alternative to cottonseed protein isolate for adhesive applications. The washing process was recently scaled up and shown to be feasible for production and practical application [43].…”
Section: Isolation Proceduresmentioning
confidence: 99%